THE IMPORTANCE AND VARIOUS TYPES OF ASSESSMENT IN THE PROCESS OF TEACHING - Notirova, Z.X.; Ahmedova , Mahliyo Bahodirjon qizi (Educational Research in Universal Sciences, 2023)
This article explores modern techniques and different ways of assessing students’ performance during the teaching process. It discusses the difference of formative and summative assessment, their results, and their implications for learners. The aim is to provide educators with effective strategies to evaluate and grade students.